A Corpus-Based Analysis of Vocabulary Load and Coverage in Indonesian EFL Textbook For 8th Grade - Husna, Fanni Hanifah; Hartono, Rudi; Sakhiyya, Zulfa (LPPM Universitas Advent Indonesia, 2025)
This research examines the vocabulary profile in 8th grade Indonesian EFL textbooks published by the Indonesian Ministry of Education in 2022 through a corpus-based approach. The study is aimed to draw a vocabulary profile of high-, mid- and low-frequency based category of vocabulary levels. In addition, the research also reports the estimated number of vocabulary size required to promote an adequate reading comprehension, where 95% and 98% coverage are regarded as the threshold. The textbook examined was obtained from the Indonesian Book Information System and prepared as analyzable corpora. The corpora consist of 27188 tokens is analyzed using Range program to obtain preliminary data analysis. The first research question revealed that the textbook contains approximately 85% of high-frequency words, followed by 7% and 0.3% of mid- and low- frequency words respectively. The second research question showed that in order to reach reading comprehension threshold of 95%, the learners need the knowledge of 3000 word-families, and additional one-thousand-word families to reach 98% of text coverage. At the end, the findings of this study suggest pedagogical implication for teachers, practical implication for textbook authors, and basis for subsequent research.